Electroweak baryogenesis via bottom transport: Complementarity between LHC and future lepton collider probes - Modak, Tanmoy; Senaha, Eibun (Physics letters, 2021)
We study the complementarity between the Large Hadron Collider (LHC) and future lepton colliders in probing electroweak baryogenesis induced by an additional bottom Yukawa coupling ρbb. The context is general two Higgs doublet model (g2HDM) where such additional bottom Yukawa coupling can account for the observed baryon asymmetry of the Universe if Im(ρbb)≳0.058. We find that LHC would probe the nominal Im(ρbb) required for baryogenesis to some extent via bg→bA→bZh process if 300GeV≲mA≲450 GeV, where A is the CP-odd scalar in g2HDM. We show that future electron positron collider such as International Linear Collider with 500 GeV and 1 TeV collision energies may offer unique probe for the nominal Im(ρbb) via e+e−→Z⁎→AH process followed by A,H→bb¯ decays in four b-jets signature. For complementarity we also study the resonant diHiggs productions, which may give an insight into strong first-order electroweak phase transition, via e+e−→Z⁎→AH→Ahh process in six b-jets signature. We find that 1 TeV collision energy with O(1)ab−1 integrated luminosity could offer an ideal environment for the discovery.